Oxford new syllabus primary mathematics workbook 3B - Yee, Dr Foong Pui
Oxford New Syllabus Primary Mathematics Workbook 3B is a mathematics workbook designed for primary school students. It provides exercises and activities that reinforce key mathematical concepts taught in class. The book covers topics such as addition, subtraction, multiplication, division, measurement, geometry, and problem-solving. It aims to help students develop a strong foundation in mathematics through a variety of practice problems, helping them build confidence and skills. The workbook is structured to support learning with clear explanations and illustrations, making math both engaging and understandable for young learners.
Keywords: Math : Textbook